Characteristic analysis of mold level fluctuation during continuous casting of Ti-bearing IF steel - Wang, Zhendong; Shan, Qinglin; Cui, Heng; Pan, Hongwei; Lu, Boxun; Shi, Xiaowei; Wen, Juwen (Journal of materials research and technology, 2024)
Mold level fluctuation has always been one of the key factors in slab quality control. Abnormal fluctuations can easily cause slag entrainment and form surface defects of hot-rolled and cold-rolled steel sheets, thus reducing the product qualification rate. In this study, mold level fluctuation data was collected during Ti-bearing Interstitial Free (IF) steel in a stable state for a complete casting sequence in a certain factory. The mold level fluctuation is analyzed using the discrete wavelet transform (DWT) method, and its characteristic values are classified based on frequency. Combined with the corresponding process parameters, the causes were traced during abnormal fluctuation characteristic values. It was found that the formation of abnormal mold level fluctuation mainly comes from two aspects. On the one hand, there are random fluctuations in the low-frequency band, and on the other, there are clustered fluctuations in the relatively high-frequency band. There is always a rising trend in mold liquid levels when there are random abnormal fluctuations in the low-frequency band. There is a delay of approximately 0.1412 s in the feedback of the stopper rod to the mold level fluctuation. The major causes of the low-frequency random fluctuations include variations in the tundish weight, casting speed, and mold width, and the clogs peeling. The clogging of the side hole at the submerged entry nozzle (SEN) is the primary cause of abnormal clustered fluctuations in the high-frequency band. These are certain relationships with clogging, whether it is high-frequency clustered or low-frequency random abnormal fluctuations. Without a doubt, this is a crucial link that limits the slab quality.